The Big Shift in Working Arrangements: Eight Ways Unusual - Steven J. Davis (Institute of Labor Economics (IZA), 2024)
The COVID-19 pandemic instigated a big shift in working arrangements. I first describe the scale of this shift in the United States, drawing on the Survey of Working Arrangements and Attitudes and other sources. I then review differences, circa 2023, in work-from-home rates across industries, demographic groups, and countries. The big shift had surprisingly benign (or even positive) effects on productivity, which is one reason it has endured. Compared to other shocks that strike modern economies, the big shift is also unusual in other respects: It relaxes time budget constraints, improves flexibility in time use, enhances individual autonomy, relaxes locational constraints, drives a major re-sorting of workers to jobs and employers, and alters the structure of wages. The big shift also reduces wage-growth pressures during the transition to new working arrangements and life styles. The shift benefits workers, on average, even as it lowers non-labor costs and real product wages for firms.
Keywords: D2; D83; E24; J22; J31; 330; COVID-19; work from home; remote work; productivity; job amenities; time savings; flexibility in time use; personal autonomy; locational constraints; Great Re-Sorting; wages